Multiply.Use the distributive property. A) 3(x-2y)
1 Answer | Add Yours
The distributive property states that:
Applying this to the above problems result to:
(A.) `3(x-2y) = 3*x -2y*3= 3x - 6y`
Hence, `3(x-2y)= 3x - 6y` .
(B) `-(x - 3y)`
A negative outside the parenthesis is the same as multiplying the expression inside the parenthesis with -1.
`=-1(x-3y) = -1*x -3y*(-1)= -x+3y=3y-x`
Hence, `-(x-3y)=3y-x` .
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes